2013
DOI: 10.1179/2045772312y.0000000048
|View full text |Cite
|
Sign up to set email alerts
|

Spinal giant cell tumor in tuberous sclerosis: Case report and review of the literature

Abstract: Background: Patients affected by tuberous sclerosis (TS) have a greater incidence of tumors than the healthy population. Spinal tumours in TS are reported very rarely and consist mainly of sacrococcygeal and cervical chordomas. Method: Case report. Findings: A 21-year-old man, affected by TS, presented a spinal dorsal T2 tumor that caused medullary compression. He underwent decompressive laminectomy and microsurgical excision of a giant cell tumor and an associated aneurysmal bone cyst. Postoperative hypofract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Other manifestations like bone cysts have been encountered occasionally. [35] Though our study revealed a high incidence of extracutaneous manifestations, apart from epilepsy and mental retardation no other complications were observed. However, only long-term follow-up will reveal the progression of the disease process and future complications.…”
Section: Retinal Achromic Patch 3 (15)mentioning
confidence: 53%
“…Other manifestations like bone cysts have been encountered occasionally. [35] Though our study revealed a high incidence of extracutaneous manifestations, apart from epilepsy and mental retardation no other complications were observed. However, only long-term follow-up will reveal the progression of the disease process and future complications.…”
Section: Retinal Achromic Patch 3 (15)mentioning
confidence: 53%
“…It is caused by pathogenic variants in either of the TSC1 or TSC2 genes resulting in the loss of functioning protein products hamartin or tuberin, respectively, and subsequent constitutive activation of mammalian target of rapamycin complex 1 (mTORC1) [2,3]. The increased mTOR activation results in benign tumor growth in various organs of the body, mainly the brain, kidneys, skin, lungs, eyes, and liver [2,3], although there have been reports of other less common organ involvement such as bone and pancreas [4,5]. Neurologic involvement is the most common cause of morbidity in this condition, with epilepsy developing in up to 90% of patients with TSC, often within the first year of life [6,7].…”
Section: Introductionmentioning
confidence: 99%